Surgical management of a sinonasal angiomatous polyp and associated cyst involving the paranasal sinuses and nasal cavity via standing axial rhinotomy. (21st March 2020) - Rowley, K. J.; Fiske‐Jackson, A. R.; Williams, J. M.; Jones, A. L.; Townsend, N. B.
Summary: This case report describes the successful surgical management of a sinonasal angiomatous polyp involving the dorsal conchal bullae, dorsal conchal sinus, ventral conchal sinus, ventral conchal bullae and ventral conchal recess of the left nasal cavity resulting in a secondary sinusitis and compression of the nasal passage.